2011
DOI: 10.1007/s10151-011-0796-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review comparing transanal haemorrhoidal de-arterialisation to stapled haemorrhoidopexy in the management of haemorrhoidal disease

Abstract: Both THD and SH are equally effective and can be attempted for the management of HD. However, THD is associated with significantly lesser postoperative pain and therefore may be considered a preferred procedure. This conclusion is based only on treating 150 patients by THD or SH in three moderate-quality randomised trials. A major, multicenter, randomised trial is required to validate this conclusion and investigate other variables like hospital stay, cost-effectiveness and health-related quality of life measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…MP inevitably creates edema and/or inflammation of the rectal mucosal and submucosa layers; this, however, can be easily controlled by administration of anti-inflammatory drugs and analgesics. The THD procedure resulted in less postoperative pain when compared to stapled hemorrhoidopexy [21,25] or conventional hemorrhoidectomy [26]. These differences could be due to the absorbable nature of the suture, avoidance of inclusion of the muscularis in the arterial ligatures, and the fact that the THD technique results in no anatomic changes of the distal rectum.…”
Section: Discussionmentioning
confidence: 92%
“…MP inevitably creates edema and/or inflammation of the rectal mucosal and submucosa layers; this, however, can be easily controlled by administration of anti-inflammatory drugs and analgesics. The THD procedure resulted in less postoperative pain when compared to stapled hemorrhoidopexy [21,25] or conventional hemorrhoidectomy [26]. These differences could be due to the absorbable nature of the suture, avoidance of inclusion of the muscularis in the arterial ligatures, and the fact that the THD technique results in no anatomic changes of the distal rectum.…”
Section: Discussionmentioning
confidence: 92%
“…With regard to DGHL, the overall recurrence rate of 17.5% is similar to that quoted for PPH (18%) and open haemorrhoidectomy (16%) . A recent limited systematic review and meta‐analysis of three randomized trials comparing PPH with DGHL found no difference in effectiveness or complications, but significantly less postoperative pain for DGHL .…”
Section: Discussionmentioning
confidence: 99%
“…Transanal hemorrhoidal deartertialization was showed to be as effective as stapled hemorrhoidopexy in terms of treatment success, complications, and incidence recurrence [83]. With an associated anopexy, this technique guarantees shortterm results similar to conventional hemorrhoidectomy with a tendency to a higher persistence of hemorrhoid prolapse [84].…”
Section: Resultsmentioning
confidence: 97%